2021
DOI: 10.1101/2021.05.25.445621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional Reprogramming of Skeletal Muscle Stem Cells by the Niche Environment

Abstract: Adult stem cells are indispensable for tissue regeneration. Tissue-specific stem cells reside in a specialized location called their niche, where they are in constant cross talk with neighboring niche cells and circulatory signals from their environment. Aging has a detrimental effect on the number and the regenerative function of various stem cells. However, whether the loss of stem cell function is a cause or consequence of their aging niche is unclear. Using skeletal muscle stem cells (MuSCs) as a model, we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 75 publications
(63 reference statements)
0
17
0
Order By: Relevance
“…Interestingly, the myoblasts used to fabricate all of the muscle tissues for this study were derived from young mice, meaning that the aged MuSCs were exposed to a young niche. We cannot rule out the possibility that the young biomimetic muscle niche partially rescued aged MuSC function, as has been reported by others ( Conboy et al, 2005 ; Lazure et al, 2022 ). Indeed, we anticipate that aged MuSCs introduced to muscle tissues fabricated from myoblasts derived from aged donors and/or exposed to an aging systemic environment will induce further functional decline.…”
Section: Discussionmentioning
confidence: 69%
“…Interestingly, the myoblasts used to fabricate all of the muscle tissues for this study were derived from young mice, meaning that the aged MuSCs were exposed to a young niche. We cannot rule out the possibility that the young biomimetic muscle niche partially rescued aged MuSC function, as has been reported by others ( Conboy et al, 2005 ; Lazure et al, 2022 ). Indeed, we anticipate that aged MuSCs introduced to muscle tissues fabricated from myoblasts derived from aged donors and/or exposed to an aging systemic environment will induce further functional decline.…”
Section: Discussionmentioning
confidence: 69%
“…Interestingly, the myoblasts used to fabricate all of the muscle tissues for this study were derived from young mice, meaning that the aged MuSCs were exposed to a young niche. We cannot rule out the possibility that the young biomimetic muscle niche partially rescued aged MuSC function, as has been reported by others 71,72 . Indeed, we anticipate that aged MuSCs introduced to muscle tissues fabricated from myoblasts derived from aged donors and/or exposed to an aging systemic environment will induce further functional decline.…”
Section: Discussionmentioning
confidence: 69%
“…Studies culturing proliferating myoblasts in conditions resembling young and old niche stiffness have shown that increased stiffness in the aged niche is associated with a decrease in the proliferation of MuSCs and, thus, reducing their regenerative capabilities [156]. A recent study using single‐cell RNA‐seq of muscle resident FAPs from young and old mice has shown that the number of FAPs is increased in the old muscle [67]. This could lead to increased ECM deposition and tissue stiffness in the aged niche [67].…”
Section: Changes In the Musc Niche During Agingmentioning
confidence: 99%
“…A recent study using single‐cell RNA‐seq of muscle resident FAPs from young and old mice has shown that the number of FAPs is increased in the old muscle [67]. This could lead to increased ECM deposition and tissue stiffness in the aged niche [67]. Accumulation of ECM and increased stiffness in aging leads to increased fibrosis which is associated with a decline in the function of MuSCs [150].…”
Section: Changes In the Musc Niche During Agingmentioning
confidence: 99%
See 1 more Smart Citation